Efektivitas Program Televisi Terhadap Perkembangan Komunikasi Orang Tua Pada Anak - Rewira, Andi Edwin; Ridwan, Muhammad (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2021)
This Research is motivated by the lack of communication between childrn and parents which has an impact on the occurrence of obstacles to the moral development of the child. This phenomenon is the effect of the advancement of mass media and the lack of attention from parents to their children. In response to this, it is necessary to conduct a study to determine the inhibiting factors of parent-child communication. thus, a solution to the existing problem will be obtained. In order to achieve these objectives in this study used qualitative-descriptive research methods with literature studies. The results of this study obtained data and fact about the negative effects caused by the mass media on the communcation relationship between children and parents as a result of the lack of parental attention to children in accessing mass media